The effect mechanism of microstructure and impact toughness on M50 bearing steel under electroshock treatment: Experiments and atomic simulation - Long Chen; Yanli Song; Kai Wu; Junhao Hu; Lin Hua; Jue Lu (Materials & Design, 2025)
To enhance the mechanical properties of M50 bearing steel, particularly its impact toughness, a novel electroshock treatment (EST) process was proposed, and the changes in its microstructure were analyzed in detail in this study. The results indicate that when the EST time is 100 ms, EST can enhance the impact toughness of M50 by approximately 55.63 % while maintaining the tensile strength essentially unchanged. Quasi-in-situ microstructural observations reveal that EST effectively refines the microstructure, significantly reduces texture intensity, homogenizes the distribution of geometrically necessary dislocations (GNDs), and alleviates stress concentration. X-ray diffraction (XRD) results confirm that EST can reduce the density of static stored dislocations (SSDs) and adjust the ratio of edge dislocations to screw dislocations within milliseconds. Molecular dynamics atomic simulations further indicate that EST promotes local atomic rearrangement within the material and delays void nucleation during the impact process, thereby enhancing the material’s impact toughness.